Quality by design-based optimization and HP-TLC densitometric standardization of Theobroma cacao L. extract as a nutraceutical supplement - Muppayyanamath, Atith; Harish, Darasaguppe R.; Mastiholimath, Vinayak; Patil, Priyanka P.; Patil, Vishal S.; Hegde, Harsha V.; Roy, Subarna (Frontiers in Nutrition, 2025)
BackgroundOur previous studies identified the hydroalcoholic extract of defatted Theobroma cacao L. bean (CE) as a cancer-preventive and a protective agent against chemotherapeutic-induced toxicities, specifically doxorubicin-induced heart, liver, and kidney toxicities.MethodsAn analytical method for phytochemical standardization was developed, and acute oral toxicity was studied in female Wistar rats following the OECD 423 guidelines. In brief, the CE was extracted using an 80:20 alcohol–water (% v/v) mixture through cold maceration, followed by spray drying to obtain powdered CE. Utilizing a Quality by Design (QbD) approach with Design Expert (DoE) software, we optimized CE tablets via direct compression. The central composite design (CCD) included five center points, with Avicel PH − 101 and croscarmellose sodium (CCS) as factors, and disintegration time, hardness, and % loss due to friability as measurements.ResultsAmong the 13 formulations, batch F-9 emerged as the optimized one within the design space, containing 35% Avicel PH − 101 and 5% CCS. The optimized formulation exhibited a disintegration time of 5.2 min, hardness of 4.2 kg/cm2, and friability of 0.34%. Importantly, no toxic effects were found at 2,000 mg/kg in the acute oral toxicity study. CE contains vital bioactive polyphenols, including (−)-epigallocatechin-3-gallate (EGCG) and (+)-catechin (CTN). We developed a marker-based HP-TLC densitometric analysis using a mobile phase of 9:9:2 v/v [ethyl acetate: toluene: formic acid], which revealed CTN at Rf 0.49 and EGCG at Rf 0.23. This method was validated according to ICH requirements.ConclusionIn conclusion, the novel, validated HP-TLC method simultaneously detects EGCG and CTN in the cocoa extract. Tablets formulated by direct compression are safe as nutraceuticals and hold promise as supplements in palliative cancer therapy.